PENGARUH CEKAMAN KEKERINGAN TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS TANAMAN TERONG (Solanum melongena L.) - Aisyah Nurvipta Anggeliana Setiyanti; Guniarti Guniarti; Juli Santoso Pikir (Jurnal Agritechno, 2022)
Efforts to increase the production of purple eggplant on drought stressed land can be done by testing the varieties of purple eggplant that have been circulating against drought stress. The test was carried out by observing the growth parameters and yields of several varieties of purple eggplant. This study aims to determine the tolerance of several varieties of purple eggplant to drought stress. The research was carried out in a plastic house on the land of Umbut Legi Hamlet, Kemuning Village, Tarik District, Sidoarjo Regency, East Java from November 2021 to March 2022. The method used in this study was a factorial (Split-Plot Design) with 3 replications. The main plot (Main Plot) is drought stress with 3 levels, namely: a) C0, 100% moisture content of field capacity as control, b) C1, water content of 75% field capacity, c) C2, water content of 50% field capacity. While the subplots (Sub Plot) are varieties of purple eggplant with 3 levels, namely: a) V1 Antaboga-1, b) V2 Lezata F1, and c) V3 Ratih Ungu. The results showed that the Antaboga variety was more tolerant of drought as indicated by the parameters of the average plant height, number of fruit per plant per harvest period, total fruit number per plant, fruit weight per plant per harvest period, and total fruit weight harvested per plant.